2011
DOI: 10.1136/bmj.d3016
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative fluid management guided by oesophageal Doppler monitoring

Abstract: Managerial barriers consisted of silo budgeting, difficulties with preparing a business case, and fears about uncontrolled implementation. By collecting outcome data, we convinced senior managers to support and sustain investment. Clinical barriers consisted mainly of scepticism regarding clinical effectiveness and worries about training. Clinicians "championing" the technology took on responsibility for data collection, education, advocacy, and spanning boundaries. When barriers to adoption of oesophageal Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 19 publications
1
48
0
1
Order By: Relevance
“…For example, although not considered in this trial, use of oesophageal Doppler-guided goal directed fluid administration during such surgery may also be beneficial as previous evidence has suggested. [24][25][26] While a recent randomised controlled trial suggests that fluid restriction in isolation does not confer benefit, 11 even the control group in that study received less than 2500ml, suggesting that the threshold for benefit falls somewhere between the 2500ml reported in that series and the 3500ml cut-off that we report. Standardisation of the definition of restrictive fluid regimens is required to allow meta-analysis and it appears that more extreme fluid restriction beyond the range of 2500-3500ml range may confer no advantage.…”
Section: Discussionmentioning
confidence: 52%
“…For example, although not considered in this trial, use of oesophageal Doppler-guided goal directed fluid administration during such surgery may also be beneficial as previous evidence has suggested. [24][25][26] While a recent randomised controlled trial suggests that fluid restriction in isolation does not confer benefit, 11 even the control group in that study received less than 2500ml, suggesting that the threshold for benefit falls somewhere between the 2500ml reported in that series and the 3500ml cut-off that we report. Standardisation of the definition of restrictive fluid regimens is required to allow meta-analysis and it appears that more extreme fluid restriction beyond the range of 2500-3500ml range may confer no advantage.…”
Section: Discussionmentioning
confidence: 52%
“…One [6] was conducted in postoperative cardiac surgical patients -again, hardly comparable to intra-operative general surgical or orthopoedic patients -and in the other [9], the investigators concluded that they could identify no clinically significant benefit in terms of length of stay with goal directed fluid management. The other data taken into consideration by NICE come from a prospective audit [10] of the intra-operative use of the CardioQ in 626 patients undergoing a variety of surgical procedures at three different hospitals in the UK. The data from these patients were then compared with matched, historical controls selected by case review of records of patients undergoing surgery in the previous year at each of the hospitals.…”
mentioning
confidence: 99%
“…These single centre trials included a total of only 764 patients, about half of whom were controls. In addition, NICE gave some consideration to an audit [10] of a mixture of major surgical procedures that included 626 patients in whom the CardioQ was used. Two meta-analyses of data drawn principally from the same clinical trials were also taken into account [11,12].…”
mentioning
confidence: 99%
“…In summary, before-and-after studies are used in anesthesiology to evaluate the effectiveness of perioperative goal-directed therapy on patient outcome [6,[15][16][17][18][19]. A before-and-after study can give valuable insights into the feasibility and effectiveness of an intervention under real-life clinical conditions and, therefore, can complement evidence from randomized controlled trials.…”
mentioning
confidence: 99%
“…Because they are simpler to perform, require fewer resources, and bear less ethical concerns than randomized controlled trials, before-and-after studies are frequently used in perioperative research [14], and have been performed to show that perioperative goal-directed therapy can improve patient outcome in high-risk abdominal surgery patients [15][16][17][18][19].…”
mentioning
confidence: 99%